Coexistence of Substance Abuse among Emergency Department Patients Presenting with Suicidal Ideation. (29th September 2020) - Tadros, Allison; Sharon, Melinda; Crum, Michael; Johnson, Ryan; Quedado, Kimberly; Fang, Wei
Abstract : Background . Patients who are suicidal commonly seek care in the emergency department (ED). Few studies have examined the coexistence between suicidal ideation, substance abuse, and psychiatric diagnosis. Objectives . This study sought to determine how often suicidal ED patients have coexisting substance abuse and psychiatric diagnosis in addition to describing the characteristics of target population. Methods . In this retrospective cohort study, chart reviews were conducted of patients over 12 with suicidal ideation who presented to an academic ED from October 2016 to March 2017. Data abstracted included gender, age, insurance, prior psychiatric diagnoses, substances abused, presence of a suicide attempt, prior suicidality, number of ED visits in the prior year, and disposition. Both descriptive and inferential statistics were calculated. Results . There were 427 patient visits to the ED for suicidality during the study period, of which 54% were male, with a mean age of 34 years. Most patients (92%) had a psychiatric diagnosis, most commonly depression (67%). More than one psychiatric diagnosis was reported in 51% of patients, while 8% had no reported underlying psychiatric diagnosis. Substance abuse was reported in 58% of patients, including marijuana (42%) and opioids (41%). Polysubstance abuse was reported in 42%. Approximately half of the patients had three or more ED visits in the previous 12 months. Most patients were insured by Medicaid (51%), while 59% were admitted for inpatient treatment. Conclusion . Substance abuse and psychiatric diagnosis were reported frequently among patients presenting to the ED with suicidal ideation, often involving more than one substance/diagnosis. Future studies should be aimed at evaluating the relationship between these conditions and determining how to better care for this population.